The United States in Cuban Media: Framing of America Related News in Granma's Internet Archives (2019)
This chapter sets out to examine Granma newspaper's representation of the U.S. in its news contents published from March 2010 to December 2018. Based on a content analysis of 989 headlines collected from the tabloid's Internet archives, the chapter answers the following research questions (1) which frames are dominantly used in news headlines related to the United States, (2) how these frames vary with time, and (3) which concepts or terms appear most frequently in the corpus of headlines. The results of the study reveal that Granma newspaper exhibits various forms of anti-Americanism in its issues. It constantly portrays the U.S. as an interventionist/imperialist power that should be blamed for the economic, educational, and housing difficulties in Cuba. The newspaper tends to constantly highlight serious inconsistency between some positive Cuban government declarations about Cuba's relations with the U.S. It equally mostly uses the conflict frame in its coverage of U.S. news events. The chapter thus argues that U.S. news in Granma's columns is constantly slanted according to some psychological biases, two of which include the us vs. them and the capitalists vs. communists. Furthermore, the newspaper constantly uses voices from experts, organizations, or authorities to suggest that lifting the blockade is a matter of utmost urgency that depends entirely on the U.S. Government's decisions.